EFISIENSI TEKNIS DAN EKONOMIS USAHATANI UBI KAYU DI KABUPATEN LAMPUNG TENGAH - Fembriarti Erry Prasmatiwi; Ktut Murniati; Renardi Iswara (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Cassava farming in Central Lampung Regency has lower productivity than its potential. Low productivity is one of the essential farming indicators that are not efficient yet. This study investigates the income level of cassava farming, technical efficiency and factors causing inefficiency, also the economic efficiency of cassava farming. This research was conducted in the cassava center, the Terbanggi Besar District and the Terusan Nunyai District, Central Lampung. Data were collected from February - March 2021 from 84 respondents of cassava farmers. The efficiency level was analyzed using stochastic frontier Cobb-Douglas. The results obtained that cassava farming in Central Lampung Regency is profitable with cassava farming income at cash costs Rp11,620,993.22/ha and R/C is 2.46; also, income on total costs Rp6,294,761.65/ha with R/C is 1.47. While cassava farming in the study area is both technically (0.85) and economically (0.79) efficient, factors that affect technical efficiency are farmer age, education, and farming experience. It was found that farmer group members and who have access to credit will reduce inefficiency